Letter to the Editor: Variability but not admission or trends in NEWS2 score predicts clinical outcome in elderly hospitalised patients with COVID-19. Issue 1 (January 2021) - Sze, Shirley; Pan, Daniel; Williams, Caroline M.L.; Wong, Nicholas; Sahota, Amandip; Bell, David; Tang, Julian W.; Wiselka, Martin; Stephenson, Iain; Pareek, Manish
Highlights: In elderly COVID-19 inpatients, admission NEWS2 scores did not predict mortality. Of components of NEW2 score, only systolic blood pressure predicted mortality. A high variability in NEW2 score predicted mortality. NEWS2 score does not consider the degree of supplemental oxygen patients require. A more sensitive early warning score for COVID-19 is needed.